2022
DOI: 10.1097/psy.0000000000001045
|View full text |Cite
|
Sign up to set email alerts
|

Sleep and Daily Social Experiences as Potential Mechanisms Linking Social Integration to Nocturnal Blood Pressure Dipping

Abstract: ObjectiveSocially integrated individuals are at lower risk of cardiovascular disease morbidity and mortality compared with their more isolated counterparts. This association may be due, in part, to the effect of social integration on nocturnal blood pressure (BP) decline or “dipping,” a physiological process associated with decreased disease risk. However, the pathways linking social integration with nocturnal BP dipping are unknown. We sought to replicate the association between social integration and BP dipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…A total of 390 participants met all eligibility criteria and completed all study visits. Note that the sample size here is discrepant from previous publications involving this study (n = 391) (20), as one of the participants who completed the study was recently determined to have been ineligible due to shiftwork. The study was approved by the University of Pittsburgh Institutional Review Board.…”
Section: Participantsmentioning
confidence: 64%
“…A total of 390 participants met all eligibility criteria and completed all study visits. Note that the sample size here is discrepant from previous publications involving this study (n = 391) (20), as one of the participants who completed the study was recently determined to have been ineligible due to shiftwork. The study was approved by the University of Pittsburgh Institutional Review Board.…”
Section: Participantsmentioning
confidence: 64%
“…Given the heterogeneity of the studies no definitive conclusions can be made, however, the accumulated evidence suggests that sleep duration (specifically short sleep) [46,48,54], sleep fragmentation (frequent awakenings) [43,44,45], a lack of sleep depth (low N3 time) [43,44,58] and increased variability in sleep timing (irregular sleep timing) [50][51][52]57] may be associated with nocturnal BP nondipping in otherwise healthy individuals. The direction of this relationship, however, is unclear (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…In the five studies that did not fully meet the criteria, a lack of confounding factors identified was with the main factor contributing to their lower appraisal. Seven studies assessed sleep using polysomnography (PSG) [42][43][44][45][46][47][48], six used wrist actigraphy [44,45,[48][49][50][51], six used only self-report methods (e.g. sleep diaries and questionnaires) [52][53][54][55][56][57] and one used an EEG headband [58].…”
Section: Study Characteristicsmentioning
confidence: 99%
“…There is growing evidence, however, that irregular sleep habits are common in the population and that intraindividual variability in sleep (IIV) could be a key dimension of overall sleep health (8,10). Greater IIV (i.e., irregular sleep patterns) has been associated with adverse health consequences such as risk for cardiovascular disease (11,12), poor metabolic health (13,14), depression (15)(16)(17), worse stress regulation (18), worse cognitive functioning (13), greater daytime sleepiness (19), poorer academic performance (20), and greater mortality (21).…”
Section: Introductionmentioning
confidence: 99%